Socialisation du groupe-classe au temps de la distanciation sociale - Tellier, Marion (Formation et profession : revue scientifique internationale en éducation, 2020)
Positive group dynamics are essential for maintaining learner attention in virtual classrooms. This article reports on two remote learning experiments during the 2020 pandemic: remote delivery of a course that was initially held in person with a group that knew each other, and the design of an innovative remote learning module. In both cases, successful online interactions and group cohesion were achieved thanks to three pedagogical techniques based on group dynamics: getting acquainted, maintaining a group spirit, and group participation and collaboration.
Keywords: Dynamique de groupe; Group dynamics; classe virtuelle; cohesion; cohésion; interaction en ligne; online interaction; transposition; virtual classroom